Peran Guru BK dalam Mengembangkan Pemahaman Diri yang Positif pada Diri Siswa SMK N 1 Guguk - Sri Astuti Eka Putri; Alfi Rahmi; Nopita Sari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
The problem with this research is that there are some students who have not been able to understand themselves positively, where these students have not been able to recognize their potential and weaknesses and have not been able to accept their physical and psychologiocal conditions well. The aim of this research is to describe the development of students’ positive self understanding and the role of guidance and caunseling teachers in developing students’ positive self understanding. The research method used is descriptive qualitative, which is a research method that describes phenomena or events that have occurred either in the present or the past. Data collection techniques used are interviews, observations and documentation. The frist informant on the study was teacher BK and supporting informant of the study was SMK student N 1 Guguk. The results of research continuously lead to students developing positive self understanding for themselves and the development of positive self understanding in students can develop well if the students is able to apply good self understanding to himself. The role of guidance and causeling teachers in developing positive self understanding instudents is by providing guidance, guidance and causeling services on the topic of self understanding as well as providing motivation or support to students in achieving positive self understanding in thenselves. So it can be concluded that the importance the guidance and counseling services provided by guidance and causeling teachers to students in developing positive self understanding, these services are preapared based on the assessments given to students.